Agunot and Get Refusal - Saffra, Meira (Iggrot Ha'Ari, 2022)
What is get refusal and how can we solve it? How does recognizing all the factors that contribute to get refusal deepen our understanding of the issue and the possible solutions? Agunot is the plural of agunah, which translates to “chained” in Hebrew, the colloquial meaning referring to a woman. Even in the 21st century — a period of freedom and mobility never existing for women before — there are many women who are denied a Jewish divorce by their husbands: they remain “chained” and are unable to remarry. Why should we care about agunot? The circumstance of agunot impacts the wider Jewish community, and, by extension, society at large. By studying this issue in depth, the hope is that the amount of harm to women can be reduced. Discussing and publicizing the plight and stories of agunot brings awareness to the issue, and, thus, is the first step towards collective corrective prevention and action.